2012
DOI: 10.1038/ni.2210
|View full text |Cite
|
Sign up to set email alerts
|

A self-reinforcing regulatory network triggered by limiting IL-7 activates pre-BCR signaling and differentiation

Abstract: The molecular crosstalk between the interkeukin-7 receptor (IL-7R) and pre-BCR in B lymphopoiesis has been enigmatic. We demonstrate that in pre-B cells, the IL-7R, but not the pre-BCR, was coupled to the phosphatidylinositol-3-OH kinase (PI(3)K)–Akt module, signaling by which prevents Rag expression. Attenuation of IL-7 signaling resulted in up-regulation of Foxo1 and Pax5, which co-activated many pre-B cell genes, including Rag1,2 and Blnk. Induction of the latter gene enabled pre-BCR signaling via the Syk-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
251
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(262 citation statements)
references
References 38 publications
(96 reference statements)
9
251
2
Order By: Relevance
“…This is reminiscent of the synergism between pre-BCR and IL-7 signals that was revealed in previous studies. 16,33 Although signal transduction downstream of pre-BCR remains to be fully characterized, similar signaling complexes are formed following the engagement of BCR and pre-BCR. [34][35][36] Because TLR4 signaling is shown to synergize with BCR-delivered signals during the activation of mature B cells, 37,38 it would not be surprising if the TLR4 signaling pathway also interacts with pre-BCR signaling during pre-B-cell development.…”
Section: Synergism Of Lps and Il-7 Signals In The Promotion Of Pre-bcmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reminiscent of the synergism between pre-BCR and IL-7 signals that was revealed in previous studies. 16,33 Although signal transduction downstream of pre-BCR remains to be fully characterized, similar signaling complexes are formed following the engagement of BCR and pre-BCR. [34][35][36] Because TLR4 signaling is shown to synergize with BCR-delivered signals during the activation of mature B cells, 37,38 it would not be surprising if the TLR4 signaling pathway also interacts with pre-BCR signaling during pre-B-cell development.…”
Section: Synergism Of Lps and Il-7 Signals In The Promotion Of Pre-bcmentioning
confidence: 99%
“…A similar inhibitory effect was also observed in the cultures of large pre-B cells (Figure 2b), which was another IL-7-responsive population of B-cell precursors. 16 The reduced proliferative response prompted us to examine the expression of IL-7 receptors in LPS-treated cells. Indeed, culture with LPS alone caused a substantial reduction in the cell surface expression of IL-7Ra in pro-B cells ( Figure 2c) and large pre-B cells (data not shown).…”
Section: Increased Pro-b and Pre-b Cells In C3h/hej Micementioning
confidence: 99%
“…We used this cell system as a model because Irf4 Ϫ/Ϫ Irf8 Ϫ/Ϫ pre-B cells are dependent on IL-7 for proliferation in vitro, which stimulates the PI3K pathway (30) and inhibits the nuclear accumulation of endogenous Bach2. 3 By staining the cells with anti-FLAG antibodies, we found that FLAG-Bach2 was present mainly in the cytoplasmic region with an exclusion from the nuclear region in ϳ75% of the cells (Fig.…”
Section: Mutations Of Bach2 Ser-509 or Ser-535 Reduce The Mobilitymentioning
confidence: 99%
“…Ϫ/Ϫ pre-B cells were cultured as reported previously (30). In the SILAC experiment, Iscove's modified Dulbecco's medium for SILAC (Thermo Fisher Scientific) containing 10% dialyzed FBS (Thermo Fisher Scientific) and 2-mercaptoethanol was used by adding either 0.4 mM L-lysine-HCl with 0.2 mM L-arginine-HCl (Sigma) as the "light" medium or 0.4 mM L-lysine-HCl-13 C 6 with 0.2 mM L-arginineHCl-13 C 6 (Wako) as the "heavy" medium.…”
Section: Irf8mentioning
confidence: 99%
“…Autocrine IL-7 production would result in increased pro-B cell proliferation and may thereby hamper V(D)J recombination, because the Rag2 protein is unstable in cycling cells (44,45). Moreover, IL-7R signaling is also coupled to phosphatidylinositol-3-OH kinase and Akt activation, which suppresses the expression of Rag proteins as well as FoxO1, Pax5, and Ikaros (46,47). To directly examine whether enhanced IL-7R signaling in pro-B cells is associated with limited IgH locus accessibility, we analyzed V H gene usage in Tg mice in which overexpression of IL-7 is driven by the mouse MHC class II Ea promoter (48).…”
Section: Slp65mentioning
confidence: 99%